Land, Listening and Voice: Investigating Community and Media Representations of the Queensland Struggle for Land Rights and Equality. Issue 1 (November 2013) - Foxwell-Norton, Kerrie; Forde, Susan; Meadows, Michael
For the most part, the story of the Australian Indigenous land rights struggle has been told by the Australian media – media that have attracted consistent criticism for their portrayal of Indigenous Australians. On the other hand, Australia boasts a vibrant and accomplished Indigenous media sector that has also told the land rights story from a different perspective, albeit to a much smaller audience. The authors are currently a part of a research team seeking to provide a critical analysis of historical and contemporary representations of the land rights movement and the broader struggle for indigenous rights and equality in Queensland. The project seeks to challenge the prevailing dialogue by focusing on the perspectives of people who have been (and still are) involved in the land rights movement. Prioritising and exploring such alternative perspectives will not only present the opportunity to reconsider the role of media representations, but will also enable an Indigenous 'take' on them to emerge. This article presents our approach and rationale, discussing the methodological possibilities and challenges of research with Indigenous communities, which ultimately seeks to redress media imbalance and injustice by a retelling that elevates Indigenous voices, stories and pictures.